EFFECTIVENESS OF THE AUTHORITY TO ENFORCE CUSTOMARY LAW THROUGH REUSAM GAMPONG PEURADA NO 1 OF 2019 CONCERNING THE RULES OF HOUSE RENTAL - Kiran Maidian; Sulfanwandi; Muslim Abdullah (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study examines the effectiveness of customary law enforcement through Reusam Gampong Peurada Number 01 of 2019 on rental housing regulations. The main problem lies in the suboptimal implementation of customary law at the village level. This study is qualitative, specifically an empirical juridical study. Primary data were obtained through interviews with community members and officials of Peurada village. Primary legal materials were obtained from laws, Qanun Jinayat, and Qanun Reusam Gampong Peurada. There were two findings from this study. First, the enforcement of customary law in cases of Reusam Gampong Peurada violations shows synergy between preventive and curative approaches. Reusam is used for social guidance through warnings and night patrols. At the same time, serious violations, such as khalwat, are referred to Wilāyah Al-Ḥisbah (WH) for processing under the Qanun Jinayat Aceh. This reflects the simultaneous use of two legal channels. Second, Reusam Gampong Peurada has clear rules and adequate supporting facilities, but the effectiveness of its enforcement is not yet optimal. Weaknesses are evident in the lack of a monitoring system, low community participation, and a weak legal culture. Therefore, it is necessary to strengthen social and institutional aspects to support the successful implementation of Reusam.